Evaluasi Pendapatan Daerah Melalui Retribusi Pasar Kota Malang Tahun 2018-2022 - Firdiyansah, Moh Iqbal; Murdiansyah, Isnan (Shafin: Sharia Finance and Accounting Journal, 2024)
The objective of this study is to examine the mechanism of market levy collection and analyze the growth of market levy revenue from 2018 to 2022. This research employs a qualitative approach, where the data consist of descriptive narratives from reports received by the author, which are then collected and analyzed to reach valid conclusions. The findings indicate that the levy collection mechanism begins with the registration of traders, tariff setting in accordance with Regional Regulation No. 4 of 2023, and levy collection by collectors, which is then deposited into the Regional General Cash Account (RKUD) via Bank Jatim. Strict supervision is conducted through levy receipt evidence and audits by the Regional Inspectorate. The analysis of market levy revenue growth from 2018 to 2022 shows fluctuations, with a significant increase in 2019 by 12.69%, a decrease in 2020 by 25.76% due to the Covid-19 pandemic, and a recovery in 2021 and 2022 by 10.68% and 23.35%.